Biodegradable composition with low tape casting precipitation and preparation method and application thereof

By adding anti-precipitation agents and phosphite-based antioxidants to the polylactic acid biodegradable composition, combining the catalytic action of titanium and tin elements, the problem of polylactic acid precipitation in the casting process is solved, and product quality and production efficiency are improved.

CN119823547AActive Publication Date: 2025-04-15KINGFA SCI & TECH CO LTD +2

Patent Information

Application Number
CN202411992799.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-15
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

In the casting process, polylactic acid easily precipitates oligomers and is enriched on the casting roller, affecting product quality and increasing production costs.

Method used

By adding specific anti-precipitation agents and phosphite-based antioxidants, combined with the catalytic action of titanium and/or tin, metal ions are chelated to avoid catalytic degradation of polylactic acid, thereby improving the problem of casting and precipitation.

Benefits of technology

The precipitation problems of biodegradable compositions in the casting process are significantly improved, the processing stability of materials and product quality are improved, and the production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223991580000021
    Figure BDA0005223991580000021
  • Figure BDA0005223991580000022
    Figure BDA0005223991580000022
  • Figure BDA0005223991580000081
    Figure BDA0005223991580000081
Patent Text Reader

Abstract

The invention relates to a biodegradable composition with low tape casting precipitation as well as a preparation method and application of the biodegradable composition. The biodegradable composition with low tape casting precipitation is prepared from the following components in parts by weight: 69 to 91 parts of polylactic acid, 0 to 16 parts of flexible biodegradable polyester, 0 to 11 parts of filler, 0.1 to 3.1 parts of anti-precipitation agent and 0.1 to 3.1 parts of phosphite ester antioxidant. The anti-precipitation agent and the phosphite antioxidant are added into the biodegradable composition taking polylactic acid as a main body, so that the problem of tape casting precipitation of the biodegradable composition is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable plastics, and more specifically to a biodegradable composition with low casting precipitation, a preparation method and application thereof. Background Art

[0002] Biodegradable materials can be decomposed by microorganisms in the natural environment, reducing pollution to the environment, especially in solving the problem of "white pollution", which is conducive to protecting soil and water resources. Due to their different characteristics, biodegradable materials can be applied to many fields, including but not limited to soft and hard packaging, consumer goods, textile industry, agriculture, gardening, construction industry, coatings, electronics, etc.

[0003] One of the main uses of biodegradable materials is to make films, which are usually made into films through the casting process. The casting process is an efficient production method that produces non-stretched, non-directional flat extruded films through melt casting and quenching. This process has a fast production speed and high output. The transparency, glossiness, thickness uniformity, etc. of the film can be extremely excellent, which is suitable for large-scale production of biodegradable material films.

[0004] Among them, there is a problem with biodegradable materials with polylactic acid as the main resin: due to the characteristics of polylactic acid itself, polylactic acid is easy to precipitate oligomers and accumulate on the casting roller during the casting process at high temperature (200-220°C) and a certain pressure (extrusion pressure 3-5Mpa). The enrichment of precipitates on the casting roller not only affects the quality of subsequent products, but also requires regular cleaning of the casting roller, increasing production costs.

[0005] It is difficult to completely avoid the precipitation of polylactic acid during the casting process, but reducing the precipitation of degradation products during the casting process can greatly improve the processing stability of the material and the quality of the product, improve terminal production efficiency, reduce production losses, and bring huge economic benefits. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem of serious precipitation of precipitates in the casting process of biodegradable materials with polylactic acid as the main resin in the current technology, and to provide a biodegradable composition with low casting precipitation.

[0007] A further object of the present invention is to provide a method for preparing the above-mentioned biodegradable composition with low casting precipitation.

[0008] A further object of the present invention is to provide use of the above-mentioned biodegradable composition with low casting precipitation in the preparation of films.

[0009] A further object of the present invention is to provide a biodegradable film.

[0010] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0011] A biodegradable composition with low casting precipitation comprises the following components in parts by weight:

[0012]

[0013] The anti-precipitation agent is a phosphorus compound having a structure shown in Formula I or Formula II;

[0014]

[0015] Wherein, R1, R2, R3, and R4 are each independently selected from any one of -H, -OH, alkoxy, or -OM; and M is selected from an alkali metal ion, an alkaline earth metal ion, or a transition metal ion;

[0016] The total content of titanium element and / or tin element in the biodegradable composition is 35-100 ppm.

[0017] The inventors of the present invention have found that polylactic acid is prone to generate free radicals under high temperature (200-220°C) and certain pressure (3-5Mpa) conditions during the casting process, and the free radicals can cause polylactic acid to degrade into oligomers and produce precipitation. The present invention adds a phosphite antioxidant, which can react with the free radicals generated by polylactic acid during the casting process to a certain extent to reduce its decomposition rate, thereby improving the precipitation problem during the casting process of the biodegradable composition to a certain extent. However, the degree of improvement of the casting precipitation problem of the biodegradable composition by adding only a phosphite antioxidant is limited.

[0018] The inventors further discovered that by adding a specific anti-precipitation agent, the problem of cast precipitation of the biodegradable composition can be significantly improved. The reason is that the polylactic acid or other biodegradable polyesters in the biodegradable composition contain trace amounts of tin and / or titanium, and the tin and / or titanium elements not only catalyze the synthesis of polylactic acid or other polyesters, but also have a certain catalytic degradation effect on polylactic acid under high temperature and high pressure in the casting process; and the addition of a specific anti-precipitation agent can chelate the metal ions of these metal catalysts, avoiding the catalytic degradation of polylactic acid by metal catalysts, and the anti-precipitation agent and phosphite antioxidants work together to significantly improve the problem of cast precipitation of the biodegradable composition.

[0019] In the present invention, the sum of the contents of titanium and / or tin in the biodegradable composition may be 35, 40, 50, 60, 70, 80, 90 or 100 ppm.

[0020] In the present invention, polylactic acid is used as the main resin, and its content accounts for more than 70wt% of the biodegradable composition.

[0021] Preferably, the phosphorus compound having the structure shown in Formula I is at least one of a phosphate ester compound, a phosphate compound or a pyrophosphate compound.

[0022] More preferably, the phosphate ester compound includes but is not limited to at least one of triethyl phosphate, tripropyl phosphate or tributyl phosphate; the phosphate salt compound includes but is not limited to at least one of sodium dihydrogen phosphate, potassium dihydrogen phosphate or zinc dihydrogen phosphate; the pyrophosphate compound includes but is not limited to disodium dihydrogen pyrophosphate. More preferably, sodium dihydrogen phosphate is used.

[0023] Preferably, the phosphite antioxidant is at least one of triphenyl phosphite, tris[2,4-di-tert-butylphenyl]phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, tetrakis(2,4-di-tert-butylphenol)4,4'-biphenyl diphosphite, distearyl pentaerythritol diphosphite or bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

[0024] In the present invention, the polylactic acid can be obtained commercially or homemade.

[0025] Wherein, the process of making the polylactic acid is as follows:

[0026] Lactide is first reacted for 2 to 4 hours in the presence of a catalyst at 130 to 150° C. and 4,000 to 6,000 Pa, and then reacted for 1 to 5 hours at 170 to 190° C. and 80,000 to 12,000 Pa to obtain the polylactic acid.

[0027] Preferably, the molecules of the polylactic acid consist of L-lactic acid units and D-lactic acid units.

[0028] Preferably, the content of titanium and / or tin in the polylactic acid is 40-100 ppm; specifically, it may be 40, 50, 60, 70, 75, 80, 90 or 100 ppm.

[0029] Preferably, the content of D-lactic acid units in the polylactic acid is 0.5 to 6 mol%.

[0030] By regulating the content of the D-lactic acid unit in the polylactic acid within this range, the amount of casting precipitation of the biodegradable composition is less.

[0031] In the present invention, the content of D-lactic acid units in the polylactic acid can be measured by gas chromatography.

[0032] The molar content of right-handed D monomer of the polylactic acid is obtained by gas chromatography test; specifically, in the gas chromatography test, the instrument used is Agilent 8860 gas chromatograph, the chromatographic column is CP7502, the FID detector temperature is 200°C, the hydrogen flow rate is 45mL / min, the air flow rate is 450mL / min, and the split ratio is 5:1.

[0033] Preferably, the melt flow rate of the polylactic acid under the test conditions of 190° C. and 2.16 kg is 3.0 to 14.0 g / 10 min.

[0034] In the present invention, the melt flow rate of polylactic acid can be measured according to ISO 1133-1:2022.

[0035] The biodegradable composition of the present invention may further contain a flexible biodegradable polyester to improve the mechanical properties of the biodegradable composition.

[0036] Preferably, the amount of the flexible biodegradable polyester is 1 to 15 parts.

[0037] Preferably, the melt flow rate of the flexible biodegradable polyester measured at 190° C. and 2.16 kg is 1.0 to 10.0 g / 10 min.

[0038] In the present invention, the melt flow rate of the flexible biodegradable polyester may be measured according to ISO 1133-1:2022.

[0039] Preferably, the content of titanium and / or tin in the flexible biodegradable polyester is 70-120 ppm; specifically, it may be 70, 80, 90, 100, 110, or 120 ppm.

[0040] More preferably, the flexible biodegradable polyester is a copolymer of a dibasic acid and / or its ester-forming derivative and a diol.

[0041] In the present invention, the biodegradable polyester can be commercially available or homemade.

[0042] More preferably, the dibasic acid is an aliphatic dibasic acid and / or an aromatic dibasic acid.

[0043] More preferably, the aliphatic dibasic acid is at least one of succinic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid or dodecanedioic acid.

[0044] More preferably, the aromatic dibasic acid is terephthalic acid.

[0045] More preferably, the diol is at least one of butanediol, propylene glycol, ethylene glycol or pentanediol.

[0046] More preferably, the flexible biodegradable polyester is at least one of polybutylene adipate terephthalate, polybutylene sebacate terephthalate, polybutylene azelaate terephthalate, polybutylene succinate terephthalate and polybutylene succinate.

[0047] The biodegradable composition of the present invention may also be added with fillers to improve the mechanical properties and production cost of the biodegradable composition.

[0048] Preferably, the amount of the filler is 1 to 10 parts.

[0049] Preferably, the particle size D50 of the filler is 2.0-10 μm.

[0050] In the present invention, the particle size D50 of the filler is measured by referring to the method of GB / T 19077.1-2008 "Particle size analysis by laser diffraction method".

[0051] Preferably, the filler is at least one of calcium carbonate, talc, starch or kaolin.

[0052] Preferably, the amount of the anti-precipitation agent is 0.1 to 3 parts, specifically 0.1, 0.2, 0.3, 0.5, 0.8, 1.0, 1.2, 1.5, 1.8, 2.0, 2.3, 2.5, 2.8 or 3.0 parts.

[0053] Preferably, the amount of the phosphite antioxidant is 1 to 3 parts; specifically, it can be 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8 or 3.0 parts.

[0054] More preferably, the amount of the phosphite antioxidant is 1.5 to 2 parts.

[0055] Preferably, the dosage ratio of the anti-precipitation agent to the phosphite antioxidant is 1:(1.5-2).

[0056] Preferably, the biodegradable material further comprises 0.1 to 3 parts of other auxiliary agents.

[0057] Optionally, the other auxiliary agent is at least one of a lubricant or a UV stabilizer.

[0058] Usually, the dosage of each other auxiliary agent is: 0.01 to 0.3 parts by weight of lubricant, 0.1 to 3 parts by weight of UV stabilizer.

[0059] Optionally, the lubricant is at least one of stearic acid amide, ethylene bisstearamide, oleic acid amide, erucic acid amide or Fischer-Tropsch wax.

[0060] Optionally, the UV stabilizer is at least one of bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidinyl) sebacate or 2-(2-hydroxy-3-tert-butyl-5-methylphenyl)-5-(2,4-dimethylphenyl)-2H-benzotriazol-4-one.

[0061] The method for preparing the above biodegradable composition comprises the following steps:

[0062] The components are mixed and melt-extruded to obtain the biodegradable composition.

[0063] Preferably, the temperature of the melt extrusion is 150-240°C.

[0064] The application of the above biodegradable composition in the preparation of tape-casting products also falls within the protection scope of the present invention.

[0065] Preferably, the cast film product is a biodegradable film.

[0066] Compared with the prior art, the present invention has the following beneficial effects:

[0067] The invention adds an anti-precipitation agent and a phosphite antioxidant to a biodegradable composition mainly composed of polylactic acid, thereby effectively improving the casting precipitation problem of the biodegradable composition. DETAILED DESCRIPTION

[0068] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0069] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0070] Polylactic acid 1#: homemade, the preparation method is as follows: 95 parts by weight of L,L-lactide (L content ≥ 99.5%, the same below) and 5 parts by weight of meso-lactide (D content is about 50%, the same below) are mixed, a catalyst (stannous octoate) is added, and ring-opening polymerization is carried out: first, the reaction temperature is 150°C and the reaction pressure is 5000Pa for 2 hours, and then the reaction temperature is 180°C and the reaction pressure is 10000Pa for 2.6 hours (recorded as time t1); underwater pelletizing, crystallization, and drying are carried out to obtain polylactic acid 1#. The melt flow rate of polylactic acid 1# is 8g / 10min (2.16kg, 190°C), the content of D-lactic acid unit is 3mol%, and the content of tin element is 52ppm.

[0071] Polylactic acid 2#: homemade, the preparation method is different from that of polylactic acid 1# in that: the amount of L,L-lactide is 99 parts by weight, the amount of meso-lactide is 1 part by weight, the time is t1 is 4.5 hours, and the amount of catalyst added is increased. The melt flow rate of polylactic acid 2# is 3.5g / 10min (2.16kg, 190℃), the content of D-lactic acid unit is 1mol%, and the content of tin element is 70ppm.

[0072] Polylactic acid 3#: homemade, its preparation method is different from that of polylactic acid 1# in that: the amount of L,L-lactide is 91 parts by weight, the amount of meso-lactide is 9 parts by weight, and the time is t1 is 1.4 hours. The melt flow rate of polylactic acid 3# is 12g / 10min (2.16kg, 190℃), the content of D-lactic acid unit is 5mol%, and the content of tin element is 50ppm.

[0073] Polylactic acid 4#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of catalyst added is reduced, and the time t1 is 4.8 hours. The melt flow rate of polylactic acid 3# is 8g / 10min (2.16kg, 190°C), the content of D-lactic acid unit is 3mol%, and the content of tin element is 10ppm.

[0074] Polylactic acid 5#: homemade, the preparation method is different from that of polylactic acid 1# in that the amount of catalyst added is increased, and the time t1 is 1.6 hours. The melt flow rate of polylactic acid 5# is 8g / 10min (2.16kg, 190°C), the content of D-lactic acid unit is 3mol%, and the content of tin element is 152ppm.

[0075] The melt flow rate of the polylactic acid is measured according to ISO 1133-1:2022.

[0076] The content of D-lactic acid unit in the above-mentioned polylactic acid is measured by gas chromatography test, and the specific process is as follows: (1) weighing 100±10 mg of ground polylactic acid sample and placing it in a 25 mL pressurized container; (2) adding 10 mL of methanol and 1 drop of dilute sulfuric acid; (3) sealing the pressurized container and placing it in a thermostat at 150° C. for 4 hours; (4) taking out the pressurized container and opening the lid after the container cools to room temperature; (5) after filtering the sample solution through a membrane filter, transferring it to a special injection vial for gas chromatography and performing gas chromatography analysis; (6) calculating the content of D-lactic acid unit in polylactic acid according to the peak area ratio; wherein, the instrument used for gas chromatography analysis is Agilent 8860 gas chromatograph, the chromatographic column is CP7502, the FID detector temperature is 200° C., the hydrogen flow rate is 45 mL / min, the air flow rate is 450 mL / min, and the split ratio is 5:1.

[0077] Flexible biodegradable polyester 1# (PBAT): Adipic acid, 1,4-butanediol, terephthalic acid and tetrabutyl titanate are put into a 200L reactor; the molar ratio of adipic acid, 1,4-butanediol and terephthalic acid is 0.25:0.6:0.25; the mass ratio of adipic acid to tetrabutyl titanate is 2000:1; the reaction temperature is 210°C, the reaction pressure is 50KPa, and the reaction time is 2.8h, and flexible biodegradable polyester 1# is obtained. The melt flow rate of flexible biodegradable polyester 1# is 6.0g / 10min (2.16kg, 190°C), and the content of titanium is 103ppm.

[0078] Flexible biodegradable polyester 2# (PBS): 1,4-butanedioic acid, 1,4-butanediol and tetrabutyl titanate are put into a 200L reactor; the molar ratio of 1,4-butanedioic acid to 1,4-butanediol is 1:1.2; the mass ratio of 1,4-butanedioic acid to tetrabutyl titanate is 3000:1; the reaction temperature is 210°C, the reaction pressure is 50KPa, and the reaction time is 3.6h to obtain flexible biodegradable polyester 2#. The melt flow rate of flexible biodegradable polyester 2# is 3.0g / 10min (2.16kg, 190°C), and the content of titanium is 80ppm.

[0079] The content of tin and / or titanium in polylactic acid, flexible biodegradable polyester and the biodegradable compositions of the embodiments and comparative examples is tested by microwave digestion-ICP-OES method, and the unit of the measurement result is ppm, where 1ppm=0.001‰. Specifically, 0.1g of the crushed sample to be tested is weighed and placed in a microwave digestion tank, 5mL of nitric acid is added to completely immerse the sample to be tested, and then 1.0mL of hydrogen peroxide is slowly dripped in. After reacting for 2 minutes, the lid is covered, the digestion tank is sealed, and it is placed in a microwave digestion furnace for digestion. After cooling to room temperature, the solution in the digestion tank is filtered with a 0.45μm filter membrane and transferred to a volumetric flask, diluted to 50mL with distilled water, and tested using ICP-OES.

[0080] Anti-precipitation agent 1#: sodium dihydrogen phosphate, MSP2040, Lianyungang Xidu Biochemical;

[0081] Anti-precipitation agent 2#: disodium dihydrogen pyrophosphate, DHPP, Nagase;

[0082] Anti-precipitation agent 3#: triethyl phosphate, Shandong Maofa Chemical Co., Ltd.; TEP.

[0083] Phosphite antioxidant 1#: triphenyl phosphite, Zhejiang Wansheng Co., Ltd.;

[0084] Phosphite antioxidant 2#: tris[2,4-di-tert-butylphenyl]phosphite, Tianjin Lianlong New Materials Co., Ltd.;

[0085] Other antioxidants 1#: didodecyl thiodipropionate, commercially available;

[0086] Other antioxidants 2#: hindered phenol antioxidant, antioxidant 1098, commercially available;

[0087] Filler 1#: talcum powder, SL92-10-A, Guangxi Longsheng Huamei Talc Development Co., Ltd., D50 particle size 7.32 μm;

[0088] Filler 2#: talcum powder, SD-9462, Liaoning Xinda Talc Group, D50 particle size 5.87 μm;

[0089] Filler 3#: calcium carbonate, omya carb5T-JI, Omya, D50 particle size is 5.5μm.

[0090] Other additives 1#: Lubricant: ethylene bisstearamide, commercially available.

[0091] Unless otherwise specified, the components (such as other auxiliary agent 1#) selected in each parallel example and comparative example are the same commercially available products.

[0092] The biodegradable compositions of the embodiments and comparative examples of the present invention are prepared by the following preparation method:

[0093] The components are weighed according to the formula, mixed evenly, and then put into a twin-screw extruder, melt-extruded and granulated at 150-240° C. to obtain a biodegradable material.

[0094] The biodegradable compositions provided in the embodiments and comparative examples of the present invention were tested for performance according to the following test methods:

[0095] Casting precipitation test: The biodegradable composition was dried at 70℃ for 4h, and then cast on the casting machine. The feed port temperature was fixed at 175℃, the barrel temperature, melt pump zone and die head temperature were all 215℃; the casting roller temperature was 25℃; the screw speed was 90rpm, the melt pump speed was 20rpm, and the pressure closed loop was performed, and the closed loop pressure was 4MPa. The film thickness was 50 microns. Before the experiment, the transition was 30min, the casting roller was wiped clean, and the casting was continued. The precipitate on the casting roller after 1h was collected, and the collected precipitate was weighed with an electronic balance. The casting roller speed was fixed at 5m / min; the casting roller diameter was 25cm, and the roller side length was 30cm.

[0096] Examples 1 to 15

[0097] Examples 1 to 15 provide a series of biodegradable compositions, the formulations of which are shown in Table 1.

[0098] Table 1 Formulas of Examples 1 to 15 (parts by weight)

[0099]

[0100]

[0101] Table 1

[0102]

[0103] Comparative Examples 1 to 12

[0104] Comparative Examples 1 to 11 provide a series of biodegradable compositions, the formulations of which are shown in Table 2.

[0105] Table 2 Formulas of Comparative Examples 1 to 11 (parts by weight)

[0106]

[0107] Comparative Example 12

[0108] The difference between Comparative Example 12 and Example 1 is that, on the basis of Example 1, 0.032 parts by weight of stannous octoate is further added.

[0109] The properties of the biodegradable compositions of the embodiments and comparative examples were tested according to the above-mentioned test methods. The test results are shown in Table 3.

[0110] Table 3 Performance test results of the biodegradable compositions of various embodiments and comparative examples

[0111]

[0112]

[0113] From Table 3, we can see that:

[0114] The precipitation amounts of the biodegradable compositions of Examples 1 to 15 in the casting precipitation test were all below 0.5 g, indicating that the addition of an anti-precipitation agent and a phosphite antioxidant to the biodegradable composition of the present invention effectively improved the casting precipitation problem of the biodegradable composition.

[0115] In Comparative Example 1, no anti-precipitation agent is added, and the problem of cast precipitation of the obtained biodegradable composition is still serious. In Comparative Example 2, no phosphite antioxidant is added, and the problem of cast precipitation of the obtained biodegradable composition is still serious. In Comparative Example 3, an organic sulfur antioxidant is added, and the problem of cast precipitation of the obtained biodegradable composition is still serious. In Comparative Example 4, no anti-precipitation agent and phosphite antioxidant are added, and the problem of cast precipitation of the biodegradable composition is serious. In Comparative Example 5, no anti-precipitation agent is added and replaced with an equal amount of phosphite antioxidant, and in Comparative Example 6, no phosphite antioxidant is added and replaced with an equal amount of anti-precipitation agent, both of which cannot effectively improve the problem of cast precipitation of the biodegradable composition. In Comparative Example 7, a hindered phenol antioxidant is added, and the problem of cast precipitation of the obtained biodegradable composition is still serious. It can be seen from Comparative Examples 8 to 11 that when the titanium and tin contents of the biodegradable composition are not within a specific range, or when the titanium and tin contents of the biodegradable composition are not within a specific range and no anti-precipitation agent and phosphite antioxidant are added, the problem of casting precipitation is still serious. For biodegradable compositions whose titanium and / or tin contents are not within a specific range, the addition of anti-precipitation agents and phosphite antioxidants has limited improvement effects on the anti-casting precipitation of the composition; among them, the casting precipitation of Comparative Example 8 is still serious, and the reason may be: the tin content in polylactic acid is low, indicating that less tin catalyst is added during its synthesis, and less tin catalyst will lead to a higher residual monomer content in polylactic acid, and a higher residual monomer content has a certain effect on the process precipitation. Comparative Example 12 is based on Example 1, and stannous octoate is added to the composition, and the casting precipitation problem of the composition becomes serious. It can be seen that the tin and / or titanium elements added externally in the composition will also affect the casting precipitation of the composition.

[0116] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A biodegradable composition with low casting precipitation, characterized in that The composition comprises the following components in parts by weight: The anti-precipitation agent is a phosphorus compound having a structure shown in Formula I or Formula II; Wherein, R1, R2, R3, and R4 are each independently selected from any one of -H, -OH, alkoxy, or -OM; and M is selected from an alkali metal ion, an alkaline earth metal ion, or a transition metal ion; The content of titanium element and / or tin element in the biodegradable composition is 35-100 ppm.

2. The biodegradable material according to claim 1, characterized in that: The phosphorus compound is at least one of a phosphate ester compound, a phosphate compound or a pyrophosphate compound.

3. The biodegradable composition according to claim 1, characterized in that: The phosphite antioxidant is at least one of triphenyl phosphite, tris[2,4-di-tert-butylphenyl]phosphite, bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, tetrakis(2,4-di-tert-butylphenol)4,4'-biphenyl diphosphite, distearyl pentaerythritol diphosphite or bis(2,4-dicumylphenyl)pentaerythritol diphosphite.

4. The biodegradable composition according to claim 1, characterized in that: The melt flow rate of the polylactic acid under the test conditions of 190° C. and 2.16 kg is 3.0 to 14.0 g / 10 min.

5. The biodegradable composition according to claim 1, characterized in that: The melt flow rate of the flexible biodegradable polyester measured at 190° C. and 2.16 kg is 1.0 to 10.0 g / 10 min.

6. The biodegradable composition according to claim 1, characterized in that: The filler is at least one of calcium carbonate, talc, starch or kaolin.

7. The biodegradable composition according to claim 1, characterized in that: The amount of the phosphite antioxidant is 1 to 3 parts, preferably 1.5 to 2 parts.

8. The method for preparing the biodegradable composition according to any one of claims 1 to 7, characterized in that: The steps include: The components are mixed and melt-extruded to obtain the biodegradable composition.

9. Use of the biodegradable composition according to any one of claims 1 to 7 in the preparation of tape-casting products.

10. The use according to claim 9, characterized in that: The cast film product is a biodegradable film.

Citation Information

Patent Citations

  • Polylactic resin composition film and preparation method thereof

    CN102453319A

  • Completely biodegradable polylactic acid composite material, as well as preparation method and application thereof

    CN103113727A

  • Melt-stable polylactide resin compositions containing phosphite esters

    US20240174800A1

Cited By

  • Biodegradable composition having low casting precipitation, and preparation method therefor and use thereof

    WO2026144713A1